What is ethical leadership? A study to define the characteristics of ethical leadership : perspectives from Australian public and private sectors - Crews, Julie Anne (Curtin University, 2011)
A truth that's told with bad intent beats all the lies you can invent. William Blake (1757–1827)The ethical dimension of leadership has been widely acknowledged as being important in the contemporary business environment (Brown & Trevino, 2006a; Brown & Mitchell, 2010; Ciulla, 2005; Knights & O’Leary, 2005; Trevino, Hartman & Brown, 2000). Indeed, Ciulla (1998) proposed that ethics is at the ‘heart of leadership’. Many scholars have examined ethics and leadership from a normative or philosophical perspective, which suggests what leaders ought to do, rather than what they actually do (Brown, 2007).More recently, the study of ethics and leadership has been undertaken from a more socio-scientific perspective. This has led to the development and conceptualisation of the construct ethical leadership, which includes the exploration of the characteristics of ethical leadership and the identification of its antecedents and consequences (Brown & Trevino, 2006b; Brown, Trevino & Harrison, 2005; Trevino et al., 2000; Trevino, Brown & Hartman, 2003).This research poses the question: what is ethical leadership? It seeks to build on the existing body of empirical research relating to the characteristics and behaviours of ethical leaders. The inclusion of a question, which asks participants their recollections of unethical leadership, represents an important contribution to research in the area of ethics and leadership. Seventy-eight (78) senior executives, represented by diverse industry backgrounds from both the public and private sectors, participated in the research. They were drawn from two states in Australia, namely Western Australia and Victoria.This research adopted a constructivist methodology and two qualitative methods: the critical incident technique (CIT) (Flanagan, 1954) and a hypothetical vignette (Alexander & Becker, 1978; Aveyard & Woolliams, 2006; Fritzche, 2000; Trevino, 1992b). Semi-structured, face-to-face interviews were undertaken for the purpose of data collection. The qualitative software package NVivo was used to assist in the management of the research data. NVivo's principal function is that of an electronic storage and retrieval system. Before its development this process was manually carried out by researchers.First, participants were asked to recall the characteristics and behaviours of two leaders with whom they had worked: one identified as being an ethical leader and the other a less than ethical leader. Second, participants described an ethical dilemma they had experienced and managed in their role as a senior executive. Third and finally, their responses to a hypothetical vignette that contained an ethical dilemma were sought. These responses were then aligned with their own ethical dilemmas to determine whether their espoused theories (what they said they would do) were congruent with their theories-in-use (what they actually did).The principal findings that emerged in this research are as follows. Participants' recollections of ethical leadership centred on three themes: value alignment, governance and relationship-centredness. Ethical leaders are perceived to be individuals who behave with integrity, courage and trustworthiness. They are relationship-centred, and fairness and altruism are the defining features of their relationships with others. In matters of governance, ethical leaders demonstrate adherence to accountability measures and discernment in their decision-making responsibilities. These findings were opposed to recollections relating to less than ethical leaders, who are defined by deception and self-centredness. In matters of governance, the decision-making of less than ethical leaders reflected culpability and expediency. Their self-centredness was evident in their abuse of power and their self-serving behaviour.When participants' responses to the hypothetical vignette were aligned with responses to their own ethical dilemmas, incongruence was evident. That is, the action many participants said they would take in response to the hypothetical vignette did not align with what they actually did in response to their own ethical dilemmas. This incongruence was most evident in two areas. In the management of their own dilemmas, participants were strongly focused on relationships with others and did not consider withdrawing from the situation. However, in response to the hypothetical vignette, participants demonstrated a greater willingness to withdraw from the situation and placed much less emphasis on their relationship with others.Finally, this study concludes that an ethical leader is perceived as an individual whose words and actions are closely aligned (value alignment). Conversely, less than ethical leaders are characterised by deception; that is, there is misalignment between what they say and what they do.